Pengaruh Profitability, Liquidity, Leverage, Growth, Dan Stock Price Terhadap Dividend Policy - Silviana Winata, Rosmita Rasyid (Fakultas Ekonomi, Universitas Tarumanagara, 2019)
The objective of this research is to analyse the influence of profitability, liquidity, leverage, growth, and stock price on dividend policy. The indicators used in this study consisted of return on assets (ROA), current ratio (CR), debt to total assets ratio (DAR), sales growth (SG), closing price, and dividend payout ratio (DPR). Sample of this research included 34 manufacturing companies listed on Indonesia Stock Exchange (BEI) were observed for three years, 2015 until 2017. The analytical method used is multiple linear regression model. Test simultaneously shows that profitability, liquidity, leverage, growth, and stock price affect dividend policy. Partial test shows that profitability and stock price positively affect dividend policy while liquidity, leverage, and growth do not affect dividend policy